PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN SHAMPO PANTENE - Marchella Dwichandra Trixie; Agus Hermani (Jurnal Ilmu Administrasi Bisnis, 2016)
Shampoo is a beauty product used by all the society, Shampoo has an important role in helping to keep your hair healthy and clean. P&G Indonesian Company has produced a Shampoo named Pantene. Pantene has leading the Indonesian market share in 2012 – 2014 regarding Top Brand Index (TBI), however in 2015 Pantene is no longer taken place at the first position and also the percentage of Pantene’s user has declining year by year. It caused by the existence of the competitors who offer lower price with higher quality of product hence the society will switch their Shampoo to the competitors.This research aims to discover the influence of price and quality product toward customer loyalty of Pantene’s Shampoo. The sampling technique used accidental and purposive sampling. This type of research is explanatory with the help of Questionnaires and Google docs as the tools in collecting data. The amount of the sample used in this research is 100 respondents which consist of female student in Faculty of Social and Political Science, Diponegoro University, Semarang. This research used qualitative and quantitative analysis technique, quantitative analysis technique uses validity test, reliability test, correlation coefficient, coefficient of determination, simple and multiple regression analysis, significance test (t-test and F-test). The result of this research shows that price and product quality severally has significant, strong and positive influence toward customer loyalty. Two variables have been tested gradually or even together show that price (0,795) and product quality (0,753) simultaneously have strong relation with customer loyalty. Amount of the value owned by price is greater than product quality, coefficient of determination value (R²) for price is 63% and product quality is 56,7%. The suggestions in this research is the company allowed to increase the sales price if the economic condition of the society is increasing, but the company is not allowed to increase the price higher than what the competitor has offered. The company also suggested to improve their quality of product related to the suitability of the benefit which printed on the package to the benefit received by the society, the company also suggested to improve the durability of fragrance and package of Pantene Shampo so it could maintain the product quality.